Safety and efficacy of oral epigallocatechin gallate in attenuating hypertension in spontaneously hypertensive rats via modulation of the intrarenal renin-angiotensin system - Parn, Kim Wai (2023)
Epigallocatechin gallate (EGCG) has been frequently recommended as a potential antihypertensive compound. Nevertheless, multiple cases of hepatotoxicity are associated with consumption of high dose EGCG-containing health supplements. To date, there is lacking scientific evidence on the safety profile of EGCG and the underlying mechanism of its antihypertensive effects in any cardiovascular disease model. This study aimed to identify the noobserved-adverse-effect level (NOAEL) of EGCG and its possible antihypertensive effects through modulation of the intrarenal renin-angiotensin system (RAS) gene expression in spontaneously hypertensive rats (SHR). EGCG (50, 250, 500 or 1000 mg/kg b.w. i.g., once daily) was administered to SHR for 28 days. All the SHR survived with no signs of systemic toxicity. Increased alanine aminotransferase and aspartate aminotransferase levels were evident in SHR administrated with 1000 mg/kg b.w. while increased thiobarbituric acid reactive substances level were present in SHR receiving EGCG equal or higher than 500 mg/kg b.w.. However, these effects were not found in those administrated with lower doses of EGCG. Subsequently, the NOAEL of EGCG was established at 250 mg/kg b.w., and the same protocol was replicated to assess its effects on blood pressure and renal RAS-related genes in SHR. The systolic blood pressure (SBP) of the EGCG group was consistently lower than the control group. The mRNA levels of cortical Agtr2 and Ace2 and medullary Agtr2, Ace and Mas1 were upregulated while medullary Ren was downregulated in EGCG group. The Pearson correlation analysis showed that SBP reduction was associated with the changes in medullary Agtr2, Ace, and Ren. EGCG treatment exhibits antihypertensive effects through activation of intrarenal Ace and Agtr2 and suppression of Ren mediators, while a high dose of EGCG induced liver damage in SHR. In future clinical studies, liver damage biomarkers should be closely monitored to further establish the safety of the long-term use of EGCG